2020
DOI: 10.1182/bloodadvances.2019001393
|View full text |Cite
|
Sign up to set email alerts
|

AKT signaling restrains tumor suppressive functions of FOXO transcription factors and GSK3 kinase in multiple myeloma

Abstract: The phosphatidylinositide-3 kinases and the downstream mediator AKT drive survival and proliferation of multiple myeloma (MM) cells. AKT signaling is active in MM and has pleiotropic effects; however, the key molecular aspects of AKT dependency in MM are not fully clear. Among the various downstream AKT targets are the Forkhead box O (FOXO) transcription factors (TFs) and glycogen synthase kinase 3 (GSK3), which are negatively regulated by AKT signaling. Here we show that abrogation of AKT signaling in MM cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 69 publications
1
29
0
Order By: Relevance
“…Importantly, we have recently demonstrated that activation of FOXO induces cell cycle arrest and cell death of MM cells. In agreement, inhibition of AKT in MM cells decreased MYC expression and activity [ 65 ]. MYC-driven lymphomas in experimental mouse models almost uniformly lose ARF or p53 expression [ 61 ], and in human Burkitt lymphoma TP53 is lost in a large fraction of the cases [ 66 ].…”
Section: C-myc Deregulation In MMmentioning
confidence: 58%
See 1 more Smart Citation
“…Importantly, we have recently demonstrated that activation of FOXO induces cell cycle arrest and cell death of MM cells. In agreement, inhibition of AKT in MM cells decreased MYC expression and activity [ 65 ]. MYC-driven lymphomas in experimental mouse models almost uniformly lose ARF or p53 expression [ 61 ], and in human Burkitt lymphoma TP53 is lost in a large fraction of the cases [ 66 ].…”
Section: C-myc Deregulation In MMmentioning
confidence: 58%
“…DHODH is expressed in MM cells and is essential for cell growth, as it was demonstrated that the specific DHODH inhibitor A771726 induced a G1 cell cycle arrest in MM cell lines. Interestingly, A771726 also inhibited AKT signaling [ 141 ], which could potentially interfere with MYC expression and activity in MM cells by activating FOXO [ 65 ]. In agreement, DHODH inhibitors and DHODH knockdown downregulated MYC expression in MM cells [ 142 ].…”
Section: C-myc Deregulation In MMmentioning
confidence: 99%
“…It is well known that AKT inhibits FOXO through direct phosphorylation [ 86 , 87 ]. Notably, FOXO1 can be indirectly targeted via the action of AKT inhibitors [ 88 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a study which demonstrates how GSK-3 potentially has tumor-suppressive functions in MM; however, its activity is restrained by Akt activation, thereby resulting in the stabilization of Mcl-1 levels [ 157 ]. Another restrainer of GSK-3 in MM cells is the histone demethylase KDM4C, which is upregulated in MM patients and, when overexpressed in MM cell lines, increases β-catenin levels and activity while decreasing both the RNA and protein expression of GSK-3β [ 158 ].…”
Section: Gsk-3 Signaling In MMmentioning
confidence: 99%